Analisis Keberhasilan Penerapan E-Government Melalui Optimalisasi Pemanfaatan Teknologi Informasi-Komunikasi dan Sumber Daya Manusia Berkualitas - Misbahuddin Azzuhri (Jurnal Aplikasi Manajemen, 2012)
This research intends to analyze and describe influence of ICT quality, IT personnel quality, and interaction quality on user satisfaction in web based information system. This research become an interesting problem because there has not been consistent empirical result. This study based on the responses of 168 respondents in local government of Malang Territory. The analysis indicated that ICT quality, IT Personnel quality, and interaction quality has positive influence on effectiveness of web bases information system. This result shows that web bases information system needs the three dimensions of qualities. Based on analysis result, ICT quality does not have significant influence on system effectiveness. This means improvements made by ICT quality does not increase the user satisfaction when using web based information system. IT Personnel quality and interaction quality have significantly influence on web based information system. It means every improvements made by IT Personnel quality and interaction quality increase the user satisfaction when using web based information system. The implication of the study was relevant to system developer and analyst also academicians seeking to explain why, how, where and when user satisfaction in information system development is needed.Keywords: ICT quality, IT Personnel quality, e-government, and user satisfaction